2023
DOI: 10.1002/bse.3584
|View full text |Cite
|
Sign up to set email alerts
|

Toward low‐carbon sustainable development: Exploring the impact of digital economy development and industrial restructuring

Lisi Tan,
Zhuodong Yang,
Muhammad Irfan
et al.

Abstract: Low‐carbon sustainable development is considered an essential strategy for achieving economic growth and environmental protection, requiring a fundamental transformation of the industrial structure, including developing clean technologies, promoting energy efficiency, and adopting sustainable production and consumption patterns. Simultaneously, the evolving digital economy is acknowledged as an essential driver in optimizing the industrial structure. Therefore, can digital economy development reshape the indus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 80 publications
0
6
0
Order By: Relevance
“…Compared with other industries, the tertiary industry has greater employment elasticity, more conducive to labor absorption (Kuznets, 1971). According to Tan et al (2023), there is proof that the growth of the digital economy directly influences low-carbon sustainable development and the modernization of the industrial structure. Ren et al (2023) have observed that the implementation of technical innovation and the optimization of industrial structure can effectively facilitate the transition towards environmentally friendly practices in China's industrial sector, specifically through the use of the digital economy.…”
Section: Dep and External Structural Effectmentioning
confidence: 99%
“…Compared with other industries, the tertiary industry has greater employment elasticity, more conducive to labor absorption (Kuznets, 1971). According to Tan et al (2023), there is proof that the growth of the digital economy directly influences low-carbon sustainable development and the modernization of the industrial structure. Ren et al (2023) have observed that the implementation of technical innovation and the optimization of industrial structure can effectively facilitate the transition towards environmentally friendly practices in China's industrial sector, specifically through the use of the digital economy.…”
Section: Dep and External Structural Effectmentioning
confidence: 99%
“…Thirdly, in the context of industrial structure upgrading, digital technology plays a crucial role (Tan, et al, 2023). It has the capacity to optimize the industrial structure, propelling the development of the secondary and tertiary sectors, particularly fostering the growth of highend manufacturing (Zhang, et al, 2022).…”
Section: Theoretical Analysismentioning
confidence: 99%
“…On one hand, many studies have substantiated the favorable influence of DE on economic growth. Scholars have demonstrated that DE holds the potential to enhance the efficiency of capital, labor, and various other factors (Lincaru et al, 2018), facilitate industrial structure upgrading (Zhang et al, 2022c;Tan et al, 2024), reduce economic operation costs (Goldfarb et al, 2019), and foster TI (Ding et al, 2022), thereby promoting economic development. Niebel (2018) argue that irrespective of a country's level of development, DE is a key contributor in driving economic prosperity.…”
Section: De and Economic Developmentmentioning
confidence: 99%